Raman Spectroscopic Fingerprints of Atomically Precise Ligand Protected Noble Metal Clusters: Au38(PET)24 and Au38−xAgx(PET)24. Issue 39 (18th August 2021) - Krishnadas, Kumaranchira Ramankutty; Baghdasaryan, Ani; Kazan, Rania; Banach, Ewa; Teyssier, Jeremie; Nicu, Valentin Paul; Buergi, Thomas
Abstract: Distinct Raman spectroscopic signatures of the metal core of atomically precise, ligand‐protected noble metal nanoclusters are reported using Au38 (PET)24 and Au38− x Ag x (PET)24 (PET = 2‐phenylethanethiolate, ‐SC2 H4 C6 H5 ) as model systems. The fingerprint Raman features (occurring <200 cm −1 ) of these clusters arise due to the vibrations involving metal atoms of their Au23 or Au23− x Ag x cores. A distinct core breathing vibrational mode of the Au23 core has been observed at 90 cm −1 . Whereas the breathing mode shifts to higher frequencies with increasing Ag content of the cluster, the vibrational signatures due to the outer metal‐ligand staple motifs (between 200 and 500 cm −1 ) do not shift significantly. DFT calculations furthermore reveal weak Raman bands at higher frequencies compared to the breathing mode, which are associated mostly with the rattling of two central gold atoms of the bi‐icosahedral Au23 core. These vibrations are also observed in the experimental spectrum. The study indicates that low‐frequency Raman spectra are a characteristic fingerprint of atomically precise clusters, just as electronic absorption spectroscopy, in contrast to the spectrum associated with the ligand shell, which is observed at higher frequencies. Abstract : The Raman spectroscopic fingerprints of atomically precise, ligand‐protected noble metal clusters are reported. The fingerprint bands arise due to the distinct core breathing mode, rattling of central metal atoms, and other vibrations involving core atoms and the ligands. Raman spectroscopy becomes a new way, just as electronic absorption spectroscopy, to identify structurally distinct metal clusters.